Contention of Meaning in WhatsApp Cultural Group : A Semantic Cognitive Analysis and Its Impact for The Law - Afdhal Kusumanegara; Syihabuddin Syihabuddin; Dadang Sudana; Aceng Ruhendi Saifullah (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The discourse of interpersonal communication in social media group contains of turn adjacency and simultaneous feedback of communication. Especially in WhatsApp group, the model of communication constructs a discourse by using a certain ideological mode through linguistic features. The communication model in the WhatsApp group involves participants directly, so that it is analyzed through mental and cognition with the semantic aspects that participants use. This study aims to reveal the contention of meaning in WhatsApp group by using cognitive semantic analysis. Cognitive semantic analysis is used to examine social cognition that affects contention of meaning among participants in the group. Contention of meaning in WhatsApp group communication is analyzed in three aspects; (1) the underlying social cognition, (2) the scheme of meaning in the group, and (3) the effects of the interaction scheme. The identification of semantic elements in interpersonal communication is based on microstructure analysis of van Dijk’s model i.e., linguistic features, such as background, coherence, detail, lexicon, pronominal, and graphic elements. Based on the research findings, the dominant aspect of social cognition that underlying participants in WhatsApp group communication are knowledges, attitudes, opinions, and concerns of the group members. The contention scheme of meaning in groups produces a discourse interaction model that tends to overlap and be structured. Effects that arose from the contention of meaning is ideological dominative groups and spread of knowledge on the topic of debate on all members of the group. This study reinforces the necessity of ideological construction through the contention of meaning in cognitive semantic studies and critical discourse especially in computer-mediated discourse analysis.